Cataract surgery of eyes with previous vitrectomy: risks and benefits as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Issue 10 (October 2020) - Lundström, Mats; Dickman, Mor; Henry, Ype; Manning, Sonia; Rosen, Paul; Tassignon, Marie-José; Young, David; Stenevi, Ulf
Abstract : Cataract surgery outcomes of eyes with previous vitrectomy are presented as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Abstract : Purpose: To explore the frequency and outcomes of cataract surgery in eyes with previous vitrectomy. Setting: Fifteen European countries. Design: Retrospective cross-sectional register-based study. Methods: The European Registry of Quality Outcomes of Cataract and Refractive Surgery (EUREQUO) contains data on baseline characteristics, surgery, and follow-up for cataract surgeries. Previous vitrectomy is included as a mandatory parameter in baseline characteristics. According to the protocol for EUREQUO, consecutive cases should be reported by participating units. Results: This study included data from units in 15 European countries from 2008 to 2018; 1 715 348 cataract extractions with follow-up data were reported to EUREQUO. Previous vitrectomy was reported in 19 416 eyes comprising 1.1% of all cases. This proportion was about the same for each study year. Most patients were men, and their mean age was 64.1 years compared with 73.7 years for the rest of the database. The preoperative visual acuity was modestly worse in postvitrectomy eyes compared with the opposite (corrected distance visual acuity [CDVA] 0.45 vs 0.25, respectively). A postoperative CDVA of 0.5 or better was achieved by 82.8% of the postvitrectomy eyes compared with 95.6% for the non-postvitrectomy eyes. The absolute mean biometry prediction error for the same groups was 0.52 diopters (D) vs 0.43 D, respectively. Conclusions: Patients undergoing cataract extraction after previous vitrectomy were younger and mostly men. Their visual and refractive outcomes were slightly inferior compared with the patients without vitrectomy.